Die Siegesstele des Amasis - Jansen-Winkeln, Karl (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
Republication of the ‘Elephantine stela’ of Amasis, formerly Cairo 13/6/24/1, now in the Nubian Museum, Aswan. The inscription, in the Königsnovelle tradition, reports two episodes of the war between Apries and Amasis. The first part, dated to year 1 of Amasis, describes the counter-attack of Apries, with the help of Greek mercenaries, against the usurper Amasis (Oct./Nov. 570). Contrary to earlier assumptions, Apries’ fleet did not start from an ‘island’ ( jw ) but rather traveled down the Canopic arm ( ᶜnw ) of the Nile. The attackers were defeated by Amasis’ troops at Jmʿw . The second part concerns repulsing an invasion by Babylonian (‘Asiatic’) troops trying, in year 4 (March 567), to reinstall Apries as king, who was killed in the course of the battle.